Effects of maternal dietary vitamin E on the egg characteristics, hatchability and offspring quality of prolonged storage eggs of broiler breeder hens. Issue 5 (28th April 2020) - Yang, Jun; Ding, Xuemei; Bai, Shiping; Wang, Jianping; Zeng, Qiufeng; Peng, Huanwei; Su, Zhuowei; Xuan, Yue; Scott Fraley, Gregory; Zhang, Keying
Abstract: This research aims to evaluate the effects of maternal vitamin E (VE) dietary supplementation on the egg characteristics, hatchability and antioxidant status of the embryo and newly hatched chicks of prolonged storage eggs. A total of 576 75‐week‐old Ross 308 breeder hens were randomly allocated into three dietary VE treatments (100, 200 and 400 mg/kg) with 6 replicates of 32 hens, for a 12‐week feeding trial. At week 12, a total of 710 eggs were collected over a 5‐day period, and eggs per treatment were attributed into 5 replicates and stored for 14 days until incubation. The egg yolk, trunk and head of 7‐day‐old embryo and the serum, liver, brain and yolk sac of newly hatched chicks were sampled for the evaluation of antioxidant status. Results showed that as maternal dietary VE levels increased, yolk α‐tocopherol concentration increased ( p < .05). Compared with 100 mg/kg VE, the use of 200 and 400 mg/kg VE increased the hatchability of set/fertile eggs and total antioxidant capacity (T‐AOC) of liver and serum in chicks ( p < .05), and decreased both the early embryonic mortality and the malondialdehyde (MDA) content of trunk and head in 7‐day‐old embryos ( p < .05); moreover, 400 mg/kg VE increased the yolk T‐AOC ( p < .05) and decreased yolk and brain MDA content of chicks ( p < .05). Brain T‐AOC of chicks in 200 mg/kg VE group was improved compared to that of chicks in 100 mg/kg VE group ( p < .05). In conclusion, maternal dietary VE at 200 or 400 mg/kg could increase hatchability by decreasing early embryonic mortality and increasing the antioxidant status of egg yolk, embryo and newly hatched chicks as breeder egg storage was prolonged to 14–18 days. The suitable VE level for the broiler breeder diet was 200 mg/kg as breeder egg storage was prolonged.